Output Voltage Control of MMC-Based Microgrid Based on Voltage Fluctuation Compensation Sliding Mode Control. (20th August 2020) - Xue, Sheng; Wang, Xinggui; Li, Xiaoying
Abstract : As a novel topology of microgrid, the output voltage control of MMC half bridge series microgrid (MMC-MG) is rarely studied. In this paper, on the basis of fully analyzing the mechanism of output voltage fluctuation of MMC-MG under the condition of islanded mode, a control strategy of a hybrid energy storage system is proposed to reduce the generating module (GM) DC-link voltage fluctuation caused by the randomness of renewable energy microsource output power. Moreover, in order to further improve the stabilization of the MMC-MG output voltage and meet the requirements of fast voltage recovery and antijamming, a sliding mode controller is designed. Then, a voltage fluctuation compensation controller is designed to suppress the DC component and fundamental frequency deviation of system output voltage caused by GM DC-link voltage fluctuation. The proposed control approach is validated against simulations using MMC-MG models with 4-GM per arm. The results show that the proposed hybrid energy storage control strategy can suppress the GM DC-link voltage fluctuation, the sliding mode controller can stabilize the system output voltage when the load drastic changes, and the fluctuation compensation strategy can suppress the DC component and the fundamental frequency deviation of system output voltage.